2020
DOI: 10.1177/1049909120920230
|View full text |Cite
|
Sign up to set email alerts
|

Access to Home and Community Health Services for Older Adults With Serious, Life-Limiting Illness: A Study Protocol

Abstract: Objectives: The objective of this study is to identify contextual access factors to home and community health services for end-of-life support for older adults with serious life-limiting illness, as well as determine if access to home and community services is associated with health-care utilization. Design: This study includes an environmental scan, grey literature review, qualitative interviews, and health-care utilization analysis. This study is a subproject of the Grudzen et al. Primary Palliative Care for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In terms of contextual characteristics, service quality index of the community was the signi cant in uencing factor. As highlighted by other researchers [33,34], the health services of community are becoming increasingly important, and our study suggested that attention should be paid to the relationship between the community and health services utilization, considering the heterogeneity of different dimensions. In terms of individual characteristics, signi cant in uencing factors included educational attainment, income quantiles, self-assessed health, BMI, place of work, self-assessed health and the number of friends.…”
Section: Discussionmentioning
confidence: 59%
“…In terms of contextual characteristics, service quality index of the community was the signi cant in uencing factor. As highlighted by other researchers [33,34], the health services of community are becoming increasingly important, and our study suggested that attention should be paid to the relationship between the community and health services utilization, considering the heterogeneity of different dimensions. In terms of individual characteristics, signi cant in uencing factors included educational attainment, income quantiles, self-assessed health, BMI, place of work, self-assessed health and the number of friends.…”
Section: Discussionmentioning
confidence: 59%
“…As highlighted by several researchers [38,39], the health services in a community are becoming increasingly important, and our study suggested that attention should be paid to the relationship between the community and health service utilization, considering the heterogeneity of different dimensions. In terms of individual characteristics, significant influencing factors included educational attainment, income quantiles, self-assessed health, BMI, place of work, SAH, and the number of friends.…”
Section: Discussionmentioning
confidence: 80%
“…We collected information on 1) familiarity with local HCS, 2) helpful and desired HCS services, 3) provideridentified barriers and facilitators to HCS, and 4) procedures involved when referring to HCS. This study is a sub-project of a national multi-site, pragmatic, cluster-randomized steppedwedge trial titled Primary Palliative Care for Emergency Medicine (PRIM-ER) [15,16].…”
Section: Introductionmentioning
confidence: 99%